Synthesis of Heterogeneous Catalysts NaOH/CaO/C From Eggshells for Biodiesel Production Using Off-Grade Palm Oil - Hawa, Karfika Ainil; Helwani, Zuchra; Amri, Amun (Jurnal Rekayasa Kimia & Lingkungan, 2020)
A heterogeneous catalyst, such as Calcium Oxide (CaO), is widely used in biodiesel production due to its various advantages over homogeneous ones. The optimum condition for synthesizing this catalyst is determined by calcination temperature and mass ratio. As a result, a modification is required to increase its performance in improving the biodiesel yield. In this study, eggshell waste was modified by calcination, hydration, and dehydration methods integrated with activated carbon and NaOH. It is used as a heterogeneous base catalyst for off-grade palm oil transesterification reactions. The results shows the catalyst with the highest activity is obtained at calcination temperature of 800c and mass ratio of 7 to 3. This is achieved with transesterification reaction conditions, which include a mole ratio of methanol/oil 6 to 1, catalyst concentration of 6%-b oil, and temperature 70c for 3 hours, yielding 79.08% of the biodiesel. Additionally, CaO, Na2CO3, and Ca (OH) 2 materials were found in the catalyst with a catalyst alkalinity value of H greater than 9.3 through X-ray diffraction (XRD) analysis. Several methyl esters, such as palmitate and oleate were also found in biodiesel through Gas Chromatography-Mass Spectrometry (GC-MS) analysis.